Impact of Remittances, Foreign Direct Investment, and Official Development Assistance on Economic Growth in Morocco: An ARDL approach (Statistics, Optimization & Information Computing, 2026)
This article examines the impact of foreign direct investment (FDI), migrant remittances, and official development assistance (ODA), as well as control variables such as gross fixed capital formation and trade openness, on economic growth in Morocco between 1980 and 2022. The analysis uses the ARDL (Autoregressive Distributed Lag) model to capture short-and long-term dynamics. The results of the cointegration test confirm the existence of a long-term relationship between the variables. Moreover, the empirical results show that, in the long term, FDI and remittances contribute positively to growth, while ODA has a negative effect. In contrast, in the short term, none of these financial flows have a significant impact on growth. The article proposes recommendations aimed at maximizing the effect of financial flows, such as encouraging productive investment, improving financial inclusion, and promoting institutional reforms. Finally, it proposes directions for future research, including the use of nonlinear models and sectoral analysis of financial flows.